An entire pastoral, church-city: a dialogue between the Ecclesiology of Jürgen Moltmann and the Pastoral of José Comblin - Gonçalves, Alonso (2014)
The article brings up a proposal for dialogue Moltmann- Comblin order to unite two concepts, the ecclesiology of Jürgen Moltmann and the pastoral of José Comblin taken to the cleaners. As the main text of the German theologian, theology of hope, suffers from practical reasoning, José Comblin taken to the cleaners can contribute to a pastoral church-inclusive city. Based on the concepts of pastoral theology, the article brings up a ministry that sees challenges and dilemmas of the city besides offering support for full pastoral activities.